Mexico Urban Development : A Contribution to a National Urban Strategy, Volume 1. Main Report - World Bank (Washington, DC, 2013)
The study aims to contribute towards a national urban strategy, in an effort to maximize Mexico's cities competitiveness, and livelihoods, in the urban economists' terms - to maximize agglomeration economies, while minimizing congestions costs. The country is in a good position for this challenge: it has relatively a mature urban system, implying an overall urban population growth, and, a reasonably balanced system of cities. However, key issues affecting the competitiveness, and livelihood of its cities are identified in three broad categories: dysfunctional nexus of land management, housing markets, and urban transport; unsatisfied demand for quality basic services - water, sanitation, and waste management; and, the lack of instruments to address the growing urbanization of poverty. Thus, the study suggests elements for an urban strategy, by addressing the implementation of institutional and regulatory reform for improved urban management; development of urban poverty programs; and development of joint programs for cities of national importance. Such suggestions are in line with the programs developed by the Government, both in the National Program for Social Development 2001-2006, and in its urban strategy within the National Program for Urban Development and Territorial Management, covering the same period. The strategy sketched in this study, is properly aligned with the national criteria, namely inclusion, sustainability, competitiveness, and regional development.